Individual-level characteristics and geospatial factors associated with cervical cancer screening participation in Alberta, Canada: a population-based cross-sectional study - Jessica Law; Geneviève Jessiman-Perreault; Amanda Alberga Machado; Linan Xu; Bonnie Chiang; Huiming Yang; Lisa Allen Scott; Rizwan Shahid; Curtis Mabilangan; Alvin Li; Kamala Adhikari; Gary Teare (BMC Public Health)
Abstract Background Cervical cancer is the fourth most common cancer in women worldwide. Effective primary prevention with human papillomavirus vaccination and secondary prevention with screening can prevent most cervical cancer cases. Cervical cancer screening uptake varies among women in underserved populations. Research that adds to the understanding of the individual and geographic area-level characteristics of women and their screening status is valuable for public health intervention planning. This study aimed to identify these characteristics related to cervical cancer screening status. Methods The study population included women between the ages of 28 to 69 years in Alberta. Data was extracted from administrative health data sources and linked to the Alberta Cervical Cancer Screening Program database to determine screening status. Descriptive bivariate analysis was conducted to describe variations in cervical cancer screening statuses and individual-level sociodemographic, health system factors, and geographic characteristics. Multinomial logistic regression analysis was conducted to investigate the relationship between these characteristics and screening participation. Geospatial analyses including heat maps were used to visualize variation in screening participation across the province. Getis-Ord Gi* hot-spot analysis was used to determine the location and magnitude of spatial autocorrelation. Results The study included 933,965 eligible women. Compared with those who are currently up-to-date for screening, those who have no record of screening tend to be older (OR: 3.63; 95% CI: 3.57 to 3.70), reside in the South Zone (OR: 1.51; 95% CI: 1.47 to 1.55), were health system non-users (OR: 2.95: 95% CI: 2.86 to 3.04), did not see a general practitioner (OR: 13.86; 95% CI: 13.32 to 14.43), or had no usual provider of care (OR: 3.227; 95% CI: 3.141 to 3.315). There are statistically significant hot spots of women who are overdue or have no record of cervical cancer screening in the North, Central, and Calgary Zones. Conclusions This study found that cervical cancer screening participation varied across geographical, health system and sociodemographic characteristics and identified clusters of regions with higher proportions of women who are under-screened in Alberta, Canada. Overall, these findings will help inform the design of interventions that aims to improve cervical cancer screening participation among underserved groups.